Effects of Chronic Oestradiol, Progesterone and Medroxyprogesterone Acetate on Hippocampal Neurogenesis and Adrenal Mass in Adult Female Rats. (June 2014) - Chan, M.; Chow, C.; Hamson, D. K.; Lieblich, S. E.; Galea, L. A. M.
<x xml:space="preserve">Abstract</x> Both natural oestrogens and progesterone influence synaptic plasticity and neurogenesis within the female hippocampus. However, less is known of the impact of synthetic hormones on hippocampal structure and function. There is some evidence that the administration of the synthetic progestin, medroxyprogesterone acetate (MPA) is not as beneficial as natural progesterone and can attenuate oestrogen‐induced neuroprotection. Although the effects of oestradiol have been well studied, little is known about the effects of natural and synthetic progestins alone and in combination with oestradiol on adult neurogenesis in females. In the present study, we investigated the effects of chronic oestradiol, progesterone, MPA and the co‐administration of each progestin with oestradiol on neurogenesis within the dentate gyrus of adult ovariectomised female rats. Twenty‐four hours after a bromodeoxyuridine (BrdU; 200 mg/kg) injection, female rats were repeatedly administered either progesterone (1 or 4 mg), MPA (1 or 4 mg), oestradiol benzoate (EB), progesterone or MPA in combination with EB (10 μg), or vehicle for 21 days. Rats were perfused on day 22 and brain tissue was analysed for the number of BrdU‐labelled and Ki67 (an endogenous marker of cell proliferation)‐expressing cells. EB alone and MPA + EB significantly decreased neurogenesis and the number of surviving BrdU‐labelled cells in the dorsal region of the dentate gyrus, independent of any effects on cell proliferation. Furthermore, MPA (1 and 4 mg) and MPA + EB treated animals had significantly lower adrenal/body mass ratios and reduced serum corticosterone (CORT) levels. By contrast, progesterone + EB treated animals had significantly higher adrenal/body mass ratios and 1 mg of progesterone, progesterone + EB, and EB significantly increased CORT levels. The results of the present study demonstrate that different progestins alone and in combination with oestradiol can differentially affect neurogenesis (via cell survival) and regulation of the hypothalamic‐pituitary‐adrenal axis. These findings have implications for women using hormone replacement therapies with MPA for both neuroprotection and stress‐related disorders.